History of epidemics and preventive medicine in Algeria during the modern and contemporary period: Infectious diseases and quarantine as a model - Guedim, Tayeb (International journal of health sciences, 2024)
Since ancient historical times, and up to the present day, humanity has been exposed to many infectious and dangerous diseases, which often led to death, and claimed thousands of human lives due to the spread of infection as a result of contact with infected people and carriers of the disease. When an epidemic spreads, or what is called a pandemic, since ancient times, man has tried and worked hard to find preventive solutions to ensure his safety and limit the spread of infection among members of society, including what is known as quarantine, health isolation, and social distancing, which is considered one of the most prominent and important primary preventive measures to confront infectious diseases. In this study, we will attempt to highlight the history of epidemics and preventive medicine in Algeria in the modern and contemporary period (the Ottoman period and during French colonialism), represented by smallpox, typhus, plague, and cholera, as well as the most important preventive measures taken to limit their spread, such as quarantine.